Dietary, environmental, and genetic risk factors of Extensive Macular Atrophy with Pseudodrusen, a severe bilateral macular atrophy of middle-aged patients - Aymeric Douillard (Nature Portfolio, 2018)
Abstract EMAP (Extensive Macular Atrophy with Pseudodrusen) is a maculopathy we recently described that shares pseudodrusen and geographic atrophy with Age-related Macular Disease (AMD). EMAP differs from AMD by an earlier age of onset (50-55 years) and a characteristic natural history comprising a night blindness followed by a severe visual loss. In a prospective case-control study, ten referral centers included 115 EMAP (70 women, 45 men) patients and 345 matched controls to appraise dietary, environmental, and genetic risk factors. The incidence of EMAP (mean 2.95/1.106) was lower in Provence-Côte d’Azur with a Mediterranean diet (1.9/1.106), and higher in regions with intensive farming or industrialized activities (5 to 20/1.106). EMAP patients reported toxic exposure during professional activities (OR 2.29). The frequencies of common AMD complement factor risk alleles were comparable in EMAP. By contrast, only one EMAP patient had a rare AMD variant. This study suggests that EMAP could be a neurodegenerative disorder caused by lifelong toxic exposure and that it is associated with a chronic inflammation and abnormal complement pathway regulation. This leads to diffuse subretinal deposits with rod dysfunction and cone apoptosis around the age of 50 with characteristic extensive macular atrophy and paving stones in the far peripheral retina.